Museu da Abolição, “The Museum That We Want” (Cadernos de Sociomuseologia, 2010)
Museu da Abolição [Abolition Museum] was inaugurated in 1983 in the city of Recife, one of the largest cities of north-eastern Brazil, located in the state of Pernambuco. This state has a special place in the history of the country: it dates back to the colonization efforts, to the first interactions between Europeans and native peoples and the exploration of sugar cane production. Today, the region embodies not only Brazilian cultural wealth and diversity, but also the great social challenges of contemporary Brazil. The name of the museum is a reference to the Abolition of black slavery in Brazil at the end of the 19th century. A museum addressing abolition means more than addressing a historic fact. It means dealing with ideas on slavery, freedom, resistance, injustice. There are no museums isolated from society, whatever their social function. For a museum such as this one, which was created with the responsibility for a theme that echoes so strongly in the lives of men and women, the challenge of finding its place in the world has always been present.